PERKAWINAN SAMIN DAN DAMPAKNYA PADA STATUS HUKUM ANAK DAN PEREMPUAN - Moh. Rosyid (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This article focuses on unregistered marriage among Samin community and its disadvantages to women and children. Using qualitative method, this paper tries to answer the question on how the practice of marriage among Samin community is and what are legal consequences of their marriage. Data were collected through observation and FGD. Since the marriage is not registered, it is not legally acknowledged by the government and Samin people do not have marriage certificate. Consequently, husband’s name is not mentioned in the family registration card and in child’s birth certificate since the children are considered as born out of wedlock. However, after the Constitutional Court’s Decision on judicial review of Administrative Law, believers of faith (penghayat kepercayaan) are allowed to state so in their national identity card. Thus, Samin people try to use this opportunity to declare their religious identity and to have their marriage registered.